SPATIALLY LOCALIZED MANAGEMENT COMPANIES USING CLOUD TECHNOLOGY - Bobor, Vojislav; Milanović, Dragan D; Kefer, Petar (Journal of Applied Engineering Science, 2013)
Content - Business applications and software platforms crossing in the cloud environment. The decades ahead will be marked by a new way of communication in business environments from telecommunication field to medicine as well as industrial production and energy efficiency. Standard business applications and software with its installation and maintenance require considerable financial resources and significant spending on hardware. To address that requirement there is the need for special teams of experts to install, test and maintain the system. The new approach to cloud applications brings to this field that what is needed, a software update is automatic with an easy access to applications efficiently from anywhere on the planet.